Voices Through Stories: Exploring the Implementation of Storytelling Method in EFL Speaking Classroom in Indonesia - Carika, Berliana Ninda Putri; Suharyanto, S (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Speaking skill is an integral part of language learning, yet many students face speaking difficulties, including language anxiety, negative expectations, and lack of motivation. These issues hinder vocabulary retention, slow speaking progress, and lead to insecurity. This study aims to examine students’ perceptions of storytelling as a method to improve speaking skills in English as a Foreign Language (EFL) classrooms. Methodology: This research employed a qualitative approach, using semi-structured interviews and direct observation during storytelling activities as primary data collection methods. The data were analyzed using two theoretical frameworks: the cognitive theory of George Lakoff and Mark Johnson, which integrates cognition with perceptual and motor experiences; and Miles and Huberman’s qualitative data analysis theory to construct the conceptual framework. Secondary data were also obtained from journals and articles. Results: The findings revealed that students showed noticeable improvement in their speaking skills after participating in storytelling activities. They engaged enthusiastically and demonstrated increased confidence and vocabulary use. Storytelling was also found to be an effective pedagogical approach for enhancing speaking skills. Applications/Originality/Value: This research provides valuable insights for future studies in EFL teaching strategies, particularly in the use of storytelling. It also offers practical implications for teachers to adopt storytelling as a method to evaluate and improve students’ English-speaking abilities.